2019
DOI: 10.1039/c9nr05273a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized nanographene sheets with high antiviral activity through synergistic electrostatic and hydrophobic interactions

Abstract: Schematic representation of synergistic action of electrostatic interactions of polyglycerol sulfate and conjugated aliphatic chains to the surface of nG-PGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 45 publications
1
79
0
Order By: Relevance
“…Graphene‐based nanomaterials prevent viral infection by direct virion interaction caused by electrostatic and hydrophobic interactions (Donskyi et al., 2019; Ye et al., 2015). Studies have shown the sheet‐like structure of these nanomaterials to destroy the viral envelope (Sametband, Kalt, Gedanken, & Sarid, 2014; Ye et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Graphene‐based nanomaterials prevent viral infection by direct virion interaction caused by electrostatic and hydrophobic interactions (Donskyi et al., 2019; Ye et al., 2015). Studies have shown the sheet‐like structure of these nanomaterials to destroy the viral envelope (Sametband, Kalt, Gedanken, & Sarid, 2014; Ye et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, due to their unique properties and biocompatibility, especially non‐toxic metabolism, carbon nanomaterials including CDs,9,10,14,77 nanographene sheets,43,78 graphene quantum dots,13 have been extensively investigated and proved to have outstanding antiviral effects. They are prepared by polyglycerol, 4‐aminophenylboronic acid hydrochloride, benzoxazine, PEG‐diamine, 3‐ethoxypropylamine, curcumin, and other raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other examples that mimic the extracellular cell matrix have been reported, which include GO functionalization with polyglycerol sulfate, 32 b-cyclodextrin 33 and polyglycerol sulphate in combination with alkyl chains. 34 A main issue regarding the functionalization of GO is controlling the density and distribution of the groups attached to the surface. Gholami et al 35 developed a one-pot [2 + 1] nitrene cycloaddition reaction to functionalize graphene by 2-azido-4,6-dichloro-1,3,5-triazine ( Fig.…”
Section: Mimicking the Cell Surfacementioning
confidence: 99%